Instrumental and Methodologicalaspects of the segmentation of Regional Labour Markets Using Qualification characteristics - V. V. Harkin (Модернизация, инновация, развитие, 2019)
Purpose: the main purpose of this article is to improve forecast-oriented management of the segmentation of regional labour markets for the professions that are in greatest demand in the main groups of the All-Russian Classifier of Occupations. The following tasks should be addressed towards this goal: 1) to group Subjects of the Russian Federation and identify, on forecast basis, the influence factors behind the dynamics of the vacanciesposted; 2) todevelopatoolkitandprioritisetheinfluencefactorsestablishedandtheirinter-relationshiplevel; 3) to preparegroupingsof the regions with the maximum number of vacancies posted in the All-Russian Database of Vacancies for the most needed professions, specialities, and occupations as per the ОК 010-2014 All-Russian Classifier of Occupations using the results of two waves of longitudinal investigation; 4) to justify the methodology and toolkit for calculating the integral ratings of Subjects of the Russian Federation; 5) to find out, on an expert basis, the level of high technology employers’ interaction with job centres; and 6) to summarise the instrumental and methodologicalaspects developed and the proposed measures for qualification-based management of the segmentation of regional labour markets.Methods: this article is based on the introduction of elements of a forecast-oriented approach to employment support using the results of regular monitoring efforts by the Russian Ministry of Labour in this area.Results: the article shows that the increase in the number of the vacancies posted by employers in the “Work in Russia” All-Russian Database of Vacancies results from their active engagement with job centres, raises the level of the realisation of businesses’ needs for skilled and professional employees and relieves tensions in regional labour markets. Support of employment is closely related to labour productivity growth, particularly in high technology sectors.Conclusions and Relevance: the materials discussed in the article present elements of forecast-oriented management of job centres aimed at regional labour markets’ segments for the professions and skilled levels required by them. The studies presented develop labour market economics with a view to better regulation of demand for and supply of employees with the required qualifications in the light of the current challenges, including the digitalisation of the economy. The practical use of the results of this article will help update the practice of management of the employment authorities at the federal, inter-regional and regional levels in the light of the results of the “Labour Productivity and Support of Employment” national project that is being implemented.